How do locus of control influence business and personal success? The mediating effects of entrepreneurial competency - Hamzah, Muhammad Iskandar; Othman, Abdul Kadir (Frontiers in Psychology, 2023)
This research aims to assess the influence of locus of control on the expression of entrepreneurial competency in a small business setting. Specifically, it predicts how this can generate positive outcomes in terms of business growth, quality of life, and sustainable entrepreneurial intention. Survey responses were collected from 102 small-sized firms in Malaysia. Structural equation modeling was performed to validate a mediation model and test nine research hypotheses. The results suggested that internal locus of control indirectly affects the venturing outcomes via entrepreneurial competency, whereas external locus of control has no such consequences. Thus, it can be deduced that beliefs based on internal attributions –rather than external forces, define entrepreneurs' destiny, and their competencies serve a perpetual role in linking these beliefs to positive business performance, life satisfaction, and sustainable entrepreneurial behavior. In practical terms, policymakers may gradually shift their focus from supplying direct financial relief assistance to the owner-managers to empowering them with core competencies building programs, especially during disasters and recessions. This study unravels the complexities of the entrepreneurial psychology-competency interface and fills a gap in the literature by providing compelling evidence of the adverse consequences of relying too heavily on fate or external assistance.